Nastroje mniejszości narodowych na terenie województwa stanisławowskiego w latach 1921–1922 w świetle raportów Policji Państwowej - Franz, Maciej (1969– ) (Instytut Historii PAN, 2024)
The Treaty of Riga of 1921 set the Polish eastern border. For the next two years, it had no international recognition as regards its run in the Eastern Lesser Poland region. This, in turn, fueled the activities of the national minorities in the area, predominantly Ukrainian and Jewish minorities, who were counting on different political solutions. Social and na-tional unrest in the voivodeship of Stanisławów (now Ivano-Frankivsk in Ukraine) in 1921–1922 resulted from this uncertainty regarding the fi nality of the European border system. The Treaty of Riga only confi rmed Polish efforts and dreams in this voivodeship. For the Ukrainians and a signifi cant part of the Jewish population, this treaty had no formal signifi -cance, which is why they tried various ways to breach it.
p. 59-79
Summary in English.
Keywords: Ukrainians; Jews; Stanisławów Voivodeship; Eastern Lesser Poland; ethnic relations; Ukraine - ethnic relations - 19th c.; Ukraine - ethnic relations - 1900-1945; Małopolska Wschodnia (Poland; region) - ethnic relations; Ivano-Frankivsk - ethnic relations